2008
DOI: 10.1007/s10761-008-0070-x
|View full text |Cite
|
Sign up to set email alerts
|

Considering Multiscalar Approaches to Creolization Among Enslaved Laborers at Estate Bethlehem, St. Croix, US Virgin Islands

Abstract: Archaeological studies of plantations need to consider the scale of the historical circumstances which shape locally circumscribed Creole processes. These circumstances range from broad generalizations down to factors operating only at the local level of the individual estate. Recent excavations at Estate Lower Bethlehem, St. Croix, Virgin Islands, have recovered an artifact assemblage from a laborer village dating from the mid-eighteenth century to the first quarter of the nineteenth century, which was situat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The current research can be placed within the larger context of African Diaspora archaeology that reaches far beyond the earliest searches for Africanisms (Fairbanks ) and begins to incorporate social theories on creolization, ethnogenesis, or the formation of a unique cultural identity, as well as the interpretation of artifacts and patterns of consumption as expressions of “embedded identities,” agency, and imagination (Hauser and Armstrong , 65; Kellar ; Lenik ; Minkoff ; Mullins ; Singleton ; Weik ). Connecting concrete objects in the material world to intangible and fluid concepts such as cultural identity is a common methodology across the field of archaeology, as these objects can serve as visible symbols of culture to anchor these ideas that would otherwise remain invisible to present day society (Kellar ).…”
Section: Use Of Ceramics In Identity Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…The current research can be placed within the larger context of African Diaspora archaeology that reaches far beyond the earliest searches for Africanisms (Fairbanks ) and begins to incorporate social theories on creolization, ethnogenesis, or the formation of a unique cultural identity, as well as the interpretation of artifacts and patterns of consumption as expressions of “embedded identities,” agency, and imagination (Hauser and Armstrong , 65; Kellar ; Lenik ; Minkoff ; Mullins ; Singleton ; Weik ). Connecting concrete objects in the material world to intangible and fluid concepts such as cultural identity is a common methodology across the field of archaeology, as these objects can serve as visible symbols of culture to anchor these ideas that would otherwise remain invisible to present day society (Kellar ).…”
Section: Use Of Ceramics In Identity Formationmentioning
confidence: 99%
“…Similar archaeology projects concerning African Diaspora sites on the island of St. Croix have highlighted the impact that historical and social trends have on material culture patterns and creolization processes. Stephan Lenik's () investigation of enslaved laborers at Estate Lower Bethlehem, St. Croix, Virgin Islands, revealed that a multiscalar approach was needed when describing artifacts that are placed in the context of a multicultural creolized society such as St. Croix. He analyzed both Afro‐Crucian coarse earthenware and European ceramics to highlight the existence of local, regional, and international trade networks that were expressed in these different categories of ceramics (Lenik ).…”
Section: Use Of Ceramics In Identity Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, studies have highlighted the significance of household activities , village household organization , the use of gardens and provision grounds (Pulsipher 1994;Handler and Wallman 2014), foodways (Armstrong 1999), ceramic production, consumption, and markets (Wilkie 1999(Wilkie , 2000Loftfield 2001;Hauser , 2011aFinch 2013;Lenik 2009), religious beliefs and burial practices (Handler and Lange 1978), alcohol consumption (Smith 2008a), marronage (Agorsah 2007), localized economic activities (Gibson 2009;Handler and Wallman 2014;Galle 2011), acts of resistance (Delle , 2014, and the creation of localized "creole" cultures (Armstrong 2003;Kelly 2008), to name a few. As a framework, archaeologists have utilized a multiscalar approach to demonstrate the active roles played by the enslaved in forging lives for themselves that challenged planter control and, via these escapes, offered them access to diverse socioeconomic realms.…”
Section: Capitalism and The Plantationmentioning
confidence: 99%
“…As a framework, archaeologists have utilized a multiscalar approach to demonstrate the active roles played by the enslaved in forging lives for themselves that challenged planter control and, via these escapes, offered them access to diverse socioeconomic realms. As such, multiscalar approaches operate economically to illustrate the dialectical relationship between the local and global in emergent networks of Atlantic world capitalism in addition to positioning "the individual within broader social milieu" (Hauser 2009, p. 4; see also Curet and Hauser 2011;Lenik 2009;Hauser and Hicks 2007).…”
Section: Capitalism and The Plantationmentioning
confidence: 99%